Innovation for sustainability : small farmers facing new challenges in the evolving food systems - Brunori, Gianluca; Grando, Stefano (Research in rural sociology and development ;, 2020)
Small farms represent important components of food systems and rural areas, as sources of occupation and livelihood, factors of socio-economic diversity, cradles of grass-roots innovation and experimentation. Their capacity to adapt and to contribute positively to societal challenges depends on the strategies they can develop and their ability to innovate. The book provides an in-depth exploration of the determinants, dynamics and outcomes of rural and agricultural change processes, with a special focus on the role of small and family farming. Covering both the system and the farm level of analysis, the authors offer a comprehensive view of approaches and models capable to grasp different complementary aspects of the development trajectories followed by farms, food systems and territories facing multi-dimensional drivers of change and exposed to a range of vulnerability factors. The emerging characters and roles of innovation networks and social learning, as well as the decision-making processes at the farm level are explored in particular depth, with attention to the multi-dimensional societal expectations vis-à-vis agriculture, small farms and rural areas, with specific attention to food and nutrition security concerns.